Networking of integrated pest management: A powerful approach to address common challenges in agriculture. (November 2016) - Lamichhane, Jay Ram; Aubertot, Jean-Noël; Begg, Graham; Birch, Andrew Nicholas E.; Boonekamp, Piet; Dachbrodt-Saaydeh, Silke; Hansen, Jens Grønbech; Hovmøller, Mogens Støvring; Jensen, Jens Erik; Jørgensen, Lise Nistrup; Kiss, Jozsef; Kudsk, Per; et al.
Abstract: Integrated pest management (IPM) is facing both external and internal challenges. External challenges include increasing needs to manage pests (pathogens, animal pests and weeds) due to climate change, evolution of pesticide resistance as well as virulence matching host resistance. The complexity of designing effective pest management strategies, which rely less heavily on the use of conventional pesticides, is another external challenge. Internal challenges include organizational aspects such as decreasing trend in budget allocated to IPM research, increasing scarcity of human expertise, lack of knowledge transfer into practice and the communication gap both at country level and between countries, and lack of multi-, inter- and transdisciplinary IPM research. There is an increasing awareness that trans-national networking is one means to overcome such challenges and to address common priorities in agriculture. A large number of stakeholders (researchers, policy makers, growers and industries) are involved in the sector of crop protection, which needs to be coordinated through effective communications and dynamic collaboration to make any IPM strategy successful. Here we discuss a decade-long IPM networking experiences in Europe emphasizing how IPM research, implementation and adoption in Europe may benefit from a broader level networking. Highlights: Integrated pest management (IPM) faces both external and internal challenges. Networking is an effective means to address IPM implementation and adoption. The need of multi-, inter-, and transdisciplinary IPM research and innovation (R&I) is discussed. A decade-long IPM networking experience in Europe is discussed. European IPM networking should be linked to other IPM networking elsewhere.